Pre-competition anxiety profile of Norwegian equestrians - Helle, I.; Haugen, T.; Johansen, B. T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Athletes who have a high trait anxiety view more situations as more threatening than those with lower trait anxiety and so respond with a higher state anxiety. This is known as competitive trait anxiety (Martens et al 1990). This may lead to a problem in e.g. the communication between horse and rider, and it may affect the rider`s performance (Visser et al 2007). The aim of this study is to track the pre-competition anxiety prior to an important competition in a group of Norwegian equestrians show jumpers. Methods: 17 participants, age 10-45 (mean 19,5, SD=9,434) were chosen in this study. 48 hours before the competition they completed a 27-item questionnaire that measured subscales of cognitive and somatic anxiety, and self-confidence - CSAI-2 (Competitive State Anxiety Inventory-2) (Martens et al 1990). This procedure was repeated 24 hours, 2 hours, and 1 hour before starting the competition. Repeated measures Anova tests were performed in order to investigate potential changes in anxiety and self-confidence. Results: The results showed a statistically significant increase in somatic anxiety level (M48 = 10.9, SE48 =0.75) between 48 hours and 2 hours/1 hour before competition (M2 =12.5, SE2 = 1.04; M1 = 12.7, SE1 = 1.19), but there was no significant difference in cognitive anxiety level. Moreover, there was a significant drop in the self-confidence between 24 hours (M24 = 28.9, SE24 = 1.89) and 2 hours/1 hour before competition (M2 = 27.4, SE2 = 2.01; M1 = 26.7, SE1 = 1.99). Discussion: The results in this study revealed a significant increase in somatic anxiety level from 48 hours to hours/1 hour before competition. This was not the case for the cognitive anxiety level. This may indicate that even if you anticipate that you are tense in your body (somatic), you are not going to be tense in your brain (cognitive) as well. However, the significant drop in self-confidence among these equestrians, suggest that there is a certain relationship between the two of them. In general, no equestrians had very high cognitive or somatic anxiety level before competition. This may be explained by their competitive level (national top level) or that they simply are show jumpers and thereby used to demonstrate their skills in jumping over fences and walls (Fitzpatrick 2004).